The Shadows of the Past: Effects of Historical Group Trauma on Current Intergroup Conflicts. (April 2017) - Schori-Eyal, Noa; Klar, Yechiel; Roccas, Sonia; McNeill, Andrew
We examined associations between two orientations based on historical group trauma, a form of enduring group victimhood (Perpetual Ingroup Victimhood Orientation [PIVO]) and the belief that one's group might itself become a victimizer (Fear of Victimizing [FOV]), and attitudes, cognitions, and emotions related to intergroup conflicts. PIVO was positively and FOV was negatively related to aggressive attitudes and emotions toward the outgroup (Studies 1a-1c, Israeli–Palestinian conflict), and to the attribution of responsibility for a series of hostilities to the outgroup (Study 3, Israeli–Palestinian conflict). PIVO was negatively and FOV positively related to support for forgiveness and reconciliation (Study 2, Northern Ireland conflict). In Experimental Study 4, FOV predicted greater accuracy in remembering harm, regardless of victims' group identity, whereas PIVO was associated with reduced accuracy only when victims were Palestinians (outgroup members). Taken together, these findings indicate that both orientations have a significant impact on intergroup conflicts and their resolution.